NOZOGEOGRAPHIC SITUATION AND FACTORS INFLUENCING THEM (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article describes nozogeographical research, which is the main direction of medical geography, the combination and interaction of ecological-climatic, socio-economic, socio-biological, medical and organizational factors affecting the aggravation of the nozogeographical situation, as well as the medical-geographical factors that determine the health status of the population.